2010
DOI: 10.17221/86/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The use of indirect methods for the prediction of lucerne quality in the first cut under the conditions of Central Europe

Abstract: ABSTRACT:The goal of this study was to compare the growing degree-days (GDD) and predictive equations for alfalfa quality (PEAQ) for the prediction of lucerne quality and to test their accuracy and suitability in the first cut period in Central Bohemia. Several additional stand parameters were verified in order to increase the accuracy of the quality estimate under these environmental conditions. In 2004-2007, the measurement and sampling were repeatedly realized from the late vegetative to the early bloom sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…This could be explained by the fact, that cereal or cereal-legume mixture used as cover crops were previously utilized as a forage source with high fibre content (Hakl et al 2011), which is not sufficient for high-performing cows. These farms also harvested lucerne at the bud stage which is in line with the best forage quality declared (Hakl et al 2010, Testa et al 2011. From all management methods, only lucernegrass mixture significantly increased forage yield in accordance with the positive effect of mixture to dry matter yield (Bélanger et al 2014).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This could be explained by the fact, that cereal or cereal-legume mixture used as cover crops were previously utilized as a forage source with high fibre content (Hakl et al 2011), which is not sufficient for high-performing cows. These farms also harvested lucerne at the bud stage which is in line with the best forage quality declared (Hakl et al 2010, Testa et al 2011. From all management methods, only lucernegrass mixture significantly increased forage yield in accordance with the positive effect of mixture to dry matter yield (Bélanger et al 2014).…”
Section: Resultsmentioning
confidence: 69%
“…For forage legume crops such as lucerne, this point seems not important due to potential of nitrogen fixation (Carlsson and Huss-Danell 2003). The impact of applied technology on lucerne or lucerne-based stand yield was usually investigated under field plot experiment covering large area from advantages of lucerne grass mixture (Bélanger et al 2014), stand establishment (Norton and Koetz 2013), and population density (Lamb et al 2003) to applied harvest management (Hakl et al 2010, Testa et al 2011) in relation to ethanol (Lamb et al 2014) or biogas production (Hakl et al 2012). However relationships among technology, environment condition and yield were not directly investigated, because these studies were usually conducted in one or few sites, under a few treatments with limited explanation power regarding to interaction with environment as well as other technological factor.…”
mentioning
confidence: 99%
“…4) content in leaves barely changed with vegetation advancement, the percentage of both NDF and ADF in the stems and the whole plant increased constantly, due to a rising quantity of stems. Most research (Hakl et al, 2010;Mehrdad et al, 2004;Mueller, 1994;Overman and Scholtz, 2005;Thompson et al, 2000) showed that the rising percentage of stems has an increasingly higher influence on the NDF and ADF content in alfalfa plants.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al (2012) and Ernert (2014) recommended the first mowing at the plant height of 50 to 70 cm, due to the favourable relationship between yield and crude protein content. Hakl et al (2010) reported very similar plant height (75 to 80 cm) as the appropriate time for the first mowing of lucerne. However, the optimal harvesting time in this case was associated with the development stages buds and first flowers, because, in the later development stages, digestibility of lucerne fodder is drastically reduced (Meyer 2005).…”
Section: Plant Heightmentioning
confidence: 90%